2009
DOI: 10.3168/jds.2009-2177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of limit feeding high- and low-concentrate diets with Saccharomyces cerevisiae on digestibility and on dairy heifer growth and first-lactation performance

Abstract: Growth and digestibility were examined for heifers limit fed high- (HC; 60%) and low-concentrate (LC; 20%) diets with or without yeast culture (YC) addition in 2 experiments. A third experiment was undertaken to monitor first-lactation production of heifers limit fed HC or LC diets. In experiment 1, 32 Holstein heifers were individually fed at controlled intakes for 133 d to maintain a targeted average daily gain of 0.80 kg/d for all 4 treatments [HC; LC with and without Saccharomyces cerevisiae; Yea-Sacc(1026… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
32
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
(74 reference statements)
15
32
2
2
Order By: Relevance
“…In agreement with these observations, Lascano and Heinrichs (2009) reported lower rumen turnover rates as F:C decreased from 80:20 to 40:60 in control-fed heifers (88 to 78%, respectively) and when comparing LF to HF diets (Lascano and Heinrichs, 2011). It has also been reported that decreasing F:C increases microbial protein yield (Pina et al, 2009;Lascano et al, 2009a); it is important to notice that these experiments decreased the F:C from 80:20 to 60:40 and from 80:20 to 40:60 in the diet, respectively. This is in agreement with results from the present experiment, where LF diet had greater predicted microbial protein (544.64 vs. 371.22 g/d); however, in as HS increased in LF, microbial protein was reduced.…”
Section: Microbial Proteinsupporting
confidence: 67%
“…In agreement with these observations, Lascano and Heinrichs (2009) reported lower rumen turnover rates as F:C decreased from 80:20 to 40:60 in control-fed heifers (88 to 78%, respectively) and when comparing LF to HF diets (Lascano and Heinrichs, 2011). It has also been reported that decreasing F:C increases microbial protein yield (Pina et al, 2009;Lascano et al, 2009a); it is important to notice that these experiments decreased the F:C from 80:20 to 60:40 and from 80:20 to 40:60 in the diet, respectively. This is in agreement with results from the present experiment, where LF diet had greater predicted microbial protein (544.64 vs. 371.22 g/d); however, in as HS increased in LF, microbial protein was reduced.…”
Section: Microbial Proteinsupporting
confidence: 67%
“…Intakes of ME and CP were controlled similar across treatments in this study, as done in previous studies (Lascano et al . ; Zanton & Heinrichs ). By definition limit‐feeding usually decreases DM and OM intakes with increasing dietary concentrate levels (Lascano et al .…”
Section: Discussionmentioning
confidence: 99%
“…Animal growth, represented by BW, withers height, body length, heart girth, paunch girth, cannon circumference, hip width and hip height, were measured on two consecutive days each week approximately 1 h before feeding, and the mean values were used to account for day‐to‐day variation (Lascano et al . ). The ADG (with gut fill) was calculated from the BW averaged over 2 days every second week, and then calculated for feed efficiency (ADG/DMI, FE).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The differences of abovementioned results might be ascribed to many reasons, some researchers suggested that the dietary composition is one of the important factors (Can et al, 2007;Grochowska, Nowak, Mikula, & Kasprowiczpotocka, 2012). Previous studies have evaluated the effect of supplemental YC on digestibility and growth of ruminants under different concentrate levels (Chademana & Offer, 1990;Lascano, Zanton, Suarez-Mena, & Heinrichs, 2009); different levels of dietary protein and energy have significant effects on the YC supplementation (Deaville & Galbraith, 1992;Harris, Dorminey, Smith, Horn, & Wilcox, 1992). Carbohydrates and fats are considered to be two types of energetic substances depending on whether they can provide the substrates that is rapidly fermented into VFA in the rumen.…”
Section: Introductionmentioning
confidence: 99%